2023
DOI: 10.1038/s41598-023-44299-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of renin–angiotensin inhibitors on renal function and the clinical course in patients with decompensated cirrhosis

Tammo L. Tergast,
Marie Griemsmann,
Heiner Wedemeyer
et al.

Abstract: Patients with decompensated cirrhosis are at risk of developing acute kidney injury (AKI). Studies have suggested that inhibition of the Renin-Angiotensin System (RAS) has certain nephro- and hepatoprotective effects in patients with compensated liver disease. This study aimed to investigate the clinical impact of RAS-Inhibitors in individuals with decompensated liver cirrhosis. Overall, 1181 consecutive hospitalized patients with ascites that underwent paracentesis were considered for this retrospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Multiple studies have shown that patients with decompensated cirrhosis with ascites who take RASi experience higher rates of ESRD, and this risk has led to the widespread avoidance of RASi in this population [ 99 , 101 , 102 , 103 ]. In contrast, a recent single-center retrospective study found that there were decreased rates of severe AKI and need for hemodialysis in patients on RASi therapies [ 125 ]. The study population included patients taking RASi for a comorbid indication prior to decompensation.…”
Section: Modulation Of Classical Rasmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown that patients with decompensated cirrhosis with ascites who take RASi experience higher rates of ESRD, and this risk has led to the widespread avoidance of RASi in this population [ 99 , 101 , 102 , 103 ]. In contrast, a recent single-center retrospective study found that there were decreased rates of severe AKI and need for hemodialysis in patients on RASi therapies [ 125 ]. The study population included patients taking RASi for a comorbid indication prior to decompensation.…”
Section: Modulation Of Classical Rasmentioning
confidence: 99%
“…Some studies have compared NSBBs to ARBs with regard to their effects on portal hypertension; a narrow majority have found that ARBs offer no discernible advantage when used alone nor an additional benefit when used in combination with NSBBs [ 65 , 103 , 113 ]. The latter finding requires additional investigation, however, as RASi has been shown to reduce portal pressures, and patients in other large observational studies may have been taking concomitant NSBB therapy, given high prevalence of NSBB use in cirrhosis in general [ 124 , 125 ].…”
Section: Modulation Of Classical Rasmentioning
confidence: 99%